“Till This Moment I never Knew Myself”: Adapting Pride and Prejudice - RAGUŽ, Anđelka (Anafora, 2023)
Adaptations are always a matter of hard choices: the scriptwriter and the director have their interpretations of what an adaptation should be, very much like every reader has his/her own vision of the characters and the plot, and very rarely do the two visions coincide. This paper was inspired by the on-going debate amongst Jane Austen fans on Internet forums as to which adaptation of Pride and Prejudice is more faithful to the 1813 novel. The main two contenders appear to be the 1995 BBC mini-series starring Jennifer Ehle and Colin Firth, and Joe Wright’s 2005 film with Keira Knightley and Matthew Macfadyen in the lead roles. This paper will attempt to identify the cardinal points of Austen’s Pride and Prejudice to illustrate that both the 1995 and 2005 adaptations are faithful to the original. Furthermore, it shall look at the strengths and weaknesses of the mini-series and the feature film as genres, before analysing the respective strengths and weaknesses of the adaptations themselves. The paper will suggest that Wright’s film fully captures “the spirit” of Austen’s novel through its masterful use of point of view and symbolism in less than half the time the 1995 mini-series does.